Morphological Responses of Excitatory Prelimbic and Orbitofrontal Cortical Neurons to Excess Corticosterone in Adolescence and Acute Stress in Adulthood - Barfield, Elizabeth T.; Sequeira, Michelle K.; Parsons, Ryan G.; Gourley, Shannon L. (Frontiers in Neuroanatomy, 2020)
Considerable evidence indicates that chronic stress and excess glucocorticoids induce neuronal remodeling in prefrontal cortical (PFC) regions. Adolescence is also characterized by a structural reorganization of PFC neurons, yet interactions between stress- and age-related structural plasticity are still being determined. We quantified dendritic spine densities on apical dendrites of excitatory neurons in the medial prefrontal cortex, prelimbic subregion (PL). Densities decreased across adolescent development, as expected, and spine volume increased. Unexpectedly, exposure to excess corticosterone (CORT) throughout adolescence did not cause additional dendritic spine loss detectable in adulthood. As a positive control dendrite population expected to be sensitive to CORT, we imaged neurons in the orbitofrontal cortex (OFC), confirming CORT-induced dendritic spine attrition on basal arbors of layer V neurons. We next assessed the effects of acute, mild stress in adulthood: On PL neurons, an acute stressor increased the density of mature, mushroom-shaped spines. Meanwhile, on OFC neurons, dendritic spine volumes and lengths were lower in mice exposed to both CORT and an acute stressor (also referred to as a “double hit”). In sum, prolonged exposure to excess glucocorticoids during adolescence can have morphological and also metaplastic consequences, but they are not global. Anatomical considerations are discussed.